A novel stainless steel with intensive silver nanoparticles showing superior antibacterial property. Issue 6 (3rd June 2021) - Liu, L. T.; Li, Y. Z.; Yu, K. P.; Zhu, M. Y.; Jiang, H.; Yu, P.; Huang, M. X.
Abstract : Stainless steels (SS) are one of the most widely used, affordable materials in public areas, but suffer from a lack of antibacterial property. Unfortunately, traditional steel casting alloying strategy has limits to add Ag due to the extremely low solubility of Ag in SS. The present work demonstrates a novel powder metallurgy technology to fabricate Ag-contained SS with a unique microstructure in which the average distance between Ag particles is similar to the size of a typical bacterium, enabling the direct contact killing mechanism. Consequently, the new Ag-contained SS possesses an excellent and stable antibacterial rate of over 99%. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: A novel stainless steel containing intensive Ag particles demonstrates excellent anti-bacterial property.